2013
DOI: 10.1007/s00586-013-2753-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the cervical spine sagittal alignment in young idiopathic scoliosis: a morphological classification of 120 cases

Abstract: Purpose To analyze the relationship between the cervical spine and global spinal-pelvic alignment in young patients with idiopathic scoliosis based on a morphological classification, and to postulate the hypothesis that cervical kyphosis is a part of cervico-thoracic kyphosis in them. Methods 120 young patients with idiopathic scoliosis were recruited retrospectively between 2006 and 2011. The following values were measured and calculated: cervical angles (CA), cervico-thoracic angles (CTA), pelvic incidence (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 17 publications
9
43
0
Order By: Relevance
“…This study found that 72.4 % of the recruited subjects stood with C7 plumbline behind HA and supero-posterior corner of S1. The proportion is similar to Yu's report in scoliotic population but lower than that in Mac-Thiong's report in normal Caucasian population [12,14]. Thus, as pointed out previously, the anterior shift of C7 plumbline may indicate the risk of the development of sagittal spinal imbalance, and the possible underlying pathology should be screened and identified [14,19,25].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This study found that 72.4 % of the recruited subjects stood with C7 plumbline behind HA and supero-posterior corner of S1. The proportion is similar to Yu's report in scoliotic population but lower than that in Mac-Thiong's report in normal Caucasian population [12,14]. Thus, as pointed out previously, the anterior shift of C7 plumbline may indicate the risk of the development of sagittal spinal imbalance, and the possible underlying pathology should be screened and identified [14,19,25].…”
Section: Discussionsupporting
confidence: 81%
“…*Statistically significant at P \ 0.05. Oneway ANOVA test [11] but lower than that of Caucasian counterparts [7][8][9]12]. Besides, previous comparison studies reported similar PI between the two groups with a thoracic or lumbar curve [8,9], which was echoed by this study (Table 4).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Reciprocal changes outside of the fused segments have previously been reported for the thoracic, lumbar and pelvic regions [7][8][9][10][11]. It has also been noted that changes in global spinal alignment following surgery affect the alignment of the cervical region [12][13][14][15].…”
Section: Introductionmentioning
confidence: 89%
“…The variation of cervical alignment after surgery for sagittal imbalance has received less attention in the scientific literature. Only recently, a few papers discuss on cervical alignment after surgery for idiopathic scoliosis [10,11], or correction of sagittal imbalance in adults [12,13]. A deeper comprehension of the mechanisms and of the changes that take place at the cervical spine in sagittal malalignment and after corrective surgery is of interest to anticipate potential reciprocal influences in patients with spinal deformity.…”
Section: Discussionmentioning
confidence: 98%